MD-GAN: Multi-Discriminator Generative Adversarial Networks for Distributed Datasets - Hardy, Corentin; Le Merrer, Erwan; Sericola, Bruno (Proceedings - IEEE International Parallel and Distributed Processing Symposium, 2019)
A recent technical breakthrough in the domain of machine learning is the discovery and the multiple applications of Generative Adversarial Networks (GANs). Those generative models are computationally demanding, as a GAN is composed of two deep neural networks, and because it trains on large datasets. A GAN is generally trained on a single server. In this paper, we address the problem of distributing GANs so that they are able to train over datasets that are spread on multiple workers. MD-GAN is exposed as the first solution for this problem: we propose a novel learning procedure for GANs so that they fit this distributed setup. We then compare the performance of MD-GAN to an adapted version of federated learning to GANs, using the MNIST, CIFAR10 and CelebA datasets. MD-GAN exhibits a reduction by a factor of two of the learning complexity on each worker node, while providing better or identical performances with the adaptation of federated learning. We finally discuss the practical implications of distributing GANs.